BANKRUPTCY LAW AS A STRUCTURAL ELEMENT OF THE LEGAL SYSTEM - Avagyan, Garik; Melkonyan, Mariam (State and Law, 2025)
There is no unified approach to bankruptcy law as a structural element of the legal system, both in legal theory and in practice. In RA, there are no scientific researches in connection with the above-mentioned problem, so the aim of the work is to first of all give the substantive and theoretical characteristics of bankruptcy law, and then to try to clarify its place and role in the RA legal system. According to the authors, bankruptcy law is a complex, multi-layered and complex structural element of the legal system, which is not completely characterized by any of the structural elements of the legal system already known to legal theory. Therefore, it is proposed to introduce a new category defining the structural elements of the bankruptcy law or a similar legal system into the theory, which will fully correspond to their nature. Its implementation will have a significant impact on the development of law in theoretical and practical terms, because the clear definition of the structural element of the legal system and highlighting its relevance helps to avoid problems in legal practice, the formation of unified approaches and creates prospects for development.
Keywords: Legal system; structural element of legal system; bankruptcy law; material and procedural norms; public and private law; a complex structural element of the legal system; a differentiated form of civil litigation.